Comparison of four numerical schemes for isoperimetric constraint fractional variational problems with a-operator - Pandey R.K.; Agrawal O.P. (My University, 2025)
This paper presents a comparative study of four numerical schemes for a class of Isoperimetric Constraint Fractional Variational Problems (ICFVPs) defined in terms of an A-operator introduced recently. The A-operator is defined in a more general way which in special cases reduces to Riemann-Liouville, Caputo, Riesz-Riemann-Liouville and Riesz-Caputo, and several other fractional derivatives defined in the literature. Four different schemes, namely linear, quadratic, quadratic-linear and Bernsteins polynomials approximations, are used to obtain approximate solutions of an ICFVP. All four schemes work well, and when the number of terms approximating the solution are increased, the desired solution is achieved. Results for a modified power kernel in A-operator for different fractional orders are presented to demonstrate the effectiveness of the proposed schemes. The accuracy of the numerical schemes with respect to parameters such as fractional order α and step size h are analyzed and illustrated in detail through various figures and tables. Finally, comparative performances of the schemes are discussed. © Copyright 2015 by ASME.